Konsumsi karbohidrat dan lemak dan hubungannya dengan daya tahan jantung paru atlet sepak bola PS Semen Padang Divisi Utama PSSI Liga Bank Mandiri IX tahun 2003 - Ferry Ferry; Woro Kushartanti; Mochammad Noerhadi (Jurnal Gizi Klinik Indonesia, 2008)
Background: Football is body movement that need energy balanced for maintaining optimum cardiorespiratory endurance. Macronutrient and micronutrient are the most nutrient needed to produce energy so that athletes have maximal performance in each sport activity. Athlete’s menu must be consist of 60-70% carbohydrate and 20-25% fat of total energy.Objective: To find out the correlation between the pattern of carbohydrate and fat intake with cardiorespiratory endurance of football athletes of PS Semen Padang in the top division of PSSI Liga Bank Mandiri in 2003.Method: This research was observational with cross sectional design. The subjects were football athletes of PS Semen Padang in the top division of PSSI Liga Bank Mandiri in 2003. Variables consisted of the pattern of carbohydrate and  fat intake, and cardiorespiratory endurance. Data were analysed using univariate, bivariate, and multivariate analysis.Results: There were no significant correlation between carbohydrate (p=0.751) and fat (p=0.297) intake with cardio- respiratory endurance, while BMI (p=0.034), triglyceride (p=0.044) and body fat (p=0.007) had significant correlation with cardiorspiratory endurance. The most influential variable to cardiorespiratory endurance was body fat (OR=12.00).Conclusion: There were significant correlation between BMI, triglyceride, and body fat with cardiorespiratory endurance of football athletes of PS Semen Padang in the top division of PSSI Liga Bank Mandiri in 2003, but  there was no correlation between pattern of carbohydrate and fat intake with cardiorespiratory endurance.